2017
DOI: 10.1002/ece3.3088
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between vegetation and environment at different levels in an arid, mountainous region of China

Abstract: Vegetation patterns and spatial organization are influenced by the changing environmental conditions and human activities. However, the effect of environment on vegetation at different vegetation classification levels has been unclear. We conducted an analysis to explore the relationship between environment and vegetation in the land use/land cover (LULC), vegetation group, vegetation type, and formation and subformation levels using redundancy analysis with seven landscape metrics and 33 environmental factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
2
3
0
Order By: Relevance
“…The obvious increase in vegetation coverage in Yanchi has also been confirmed in previous research (Gao et al, 2017). The average NDVI in Yanchi had increased significantly with a rate of 52.92% from 2000 to 2015.…”
Section: Determinants Of Ndvi Changes In Case Areasupporting
confidence: 82%
See 3 more Smart Citations
“…The obvious increase in vegetation coverage in Yanchi has also been confirmed in previous research (Gao et al, 2017). The average NDVI in Yanchi had increased significantly with a rate of 52.92% from 2000 to 2015.…”
Section: Determinants Of Ndvi Changes In Case Areasupporting
confidence: 82%
“…The average NDVI in Yanchi had increased significantly with a rate of 52.92% from 2000 to 2015. The obvious increase in vegetation coverage in Yanchi has also been confirmed in previous research (Gao et al, 2017). The stepwise regression showed that the proportion of rural laborers engaged in farming activities (p < 0.05) and afforestation area (p < 0.05) were significant driving factors ( Table 2).…”
Section: Determinants Of Ndvi Changes In Case Areasupporting
confidence: 80%
See 2 more Smart Citations
“…Vegetation cover is similar on both sites of the southern slope, including the undercover and grass, which indicates the similarity of environments (sf. Dorji et al 2014;Gao et al 2017); the presence of more drought-sensitive species (e.g. Abies sibirica, Rubus idaeus and Ribes rubrum) and the absence of the more xeric Spiraea media and Caragana arborescens on the northern slope indicates a higher moisture supply there than on the southern slope (cf.…”
Section: Discussionmentioning
confidence: 99%